ANALISIS KEBUTUHAN BELAJAR TERHADAP PENGGUNAAN MEDIA MATHFUN DALAM PEMBELAJARAN MATEMATIKA BAGI DISABILITAS INTELEKTUAL - Jhozia, Vani Febri; Budi, Setia; Zulmiyetri; Syari Yuliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the need to develop MathFun as a medium or tool for teaching mathematics, specifically addition and subtraction, to students with mild intellectual disabilities at SLBN 1 Pagaruyung. The background of this study is based on the difficulties students have in understanding concepts and maintaining focus during the mathematics learning process, particularly in addition and subtraction. The research method used was descriptive qualitative with a research and development approach at the stage of needs analysis as the initial stage of the research. The results of observations and interviews with classroom teachers showed that students with intellectual disabilities still face obstacles in improving their understanding of concepts and maintaining focus in learning, which is caused by limitations in the learning media or tools applied by teachers during the learning process. Thus, this study underlines the importance of developing android-based MathFun learning media to support mathematics learning for students with mild intellectual disabilities.